Preparing Students as global citizens through strengthening state defense attitudes and actions - Mahpudz, Asep; Riandhana, Taufiq Eka; Alanur, Shofia Nurun; Syuaib, Dahlia (Universitas Negeri Malang, 2022)
Learning Citizenship Education in Higher Education faces challenges in the dynamics and global developments. One of the challenges faced in interpreting state defense for students who are young citizens. This article aims to conceptually analyze the steps to prepare students as young citizens as part of global citizens through strengthening awareness of defending the State. This study uses a quantitative descriptive research approach. Data collection techniques by distributing questionnaires randomly via google form to students of Tadulako University class 2018, 2019, and 2020 who have studied Citizenship Education. The results of the questionnaire were analyzed by percentage. The study results show that state defense's values, attitudes, and actions can be integrated into the learning of Citizenship Education in Higher Education. This is a step to strengthen students' cognitive, affective, and psychomotor aspects. That state defense is a form of student love as citizens of the State. The learning process of Citizenship Education in Higher Education, which discusses the material of state defense, is seen by students as very positive/very good and positive/good.